Teachers’ perceptions of rejection sensitivity in inclusive primary schools: qualitative case study - Elballah, Khaled; Alsayed, Abdulrahman (Frontiers in Education, 2025)
Rejection sensitivity (RS) among primary school students is a serious problem that often has multiple negative consequences including poor academic performance and mental health problems. The current study used a qualitative methodology to determine the role of teachers’ psychological awareness in preventing RS allergy in the school environment through stakeholder intervention and RS allergy prevention programs. When teachers notice students with disabilities being rejected, they can take steps to reduce it. The researcher conducted semi-structured interviews with 18 teachers working in public primary inclusive schools in Al-Ahsa, Saudi Arabia, with deaf, hard of hearing (DHH), and learning disabilities programs. The findings provide an initial step in identifying the forms and types of RS in the school context, helping administrators, teachers, parents, and students reduce the phenomenon of RS and develop long-term plans to address it. Taking teachers’ perceptions into account may enable the development and implementation of new programs to address RS directed toward individuals with disabilities in primary schools. The discussion highlights future research directions and limitations of current research.